Financial Literacy, Financial Fragility, and Financial Well-being Among Generation-Z University Students in Indonesia - Jasen, Lie; Kim, Sung Suk (University of Merdeka Malang, 2023)
This research aims to investigate the correlation between financial literacy and financial fragility as well as financial well-being, along with identifying what factors influence these three financial components. We create an online questionnaire and distribute it to 317 university students that are part of Generation-Z students in Indonesia. The data analysis method uses the logistic regression model and marginal effect analysis. The research’s findings shows that educational background of father and the behavior of recording transactions are the factors influencing financial literacy. In addition, the level of financial fragility and financial well-being has been found to be affected by the father’s education, parent’s income, and investment experience. It is also proven that financially literate people are capable of withstanding unexpected financial crisis. Finally, the result shows that financial literacy is a key to achieving financial well-being at an early age. Therefore, policy maker should be aware of this situation and increase financial education for young generations.DOI: 10.26905/jkdp.v27i2.9402